Evaluation of Surface Roughness of Nanofilled and Nanohybrid Composite Restorative Materials Utilizing Various Finishing and Polishing Systems: A Comparative In Vitro Study - Tay Hatem Kadhom (Dental Hypotheses)
Introduction: The aim was to assess and compare the surface roughness properties of nanofilled and nanohybrid resin composites using various polishing systems. Methods: A metallic mold was used to create 100 composite discs in total. Two main groups of resin composites were used (each N = 50): group I, Filtek Z350 XT (nanofilled composite) and group II, IPS Empress Direct (Nanohybrid composite). Each main group was further divided into five subgroups (each N = 10) as follows: subgroup 1 (Mylar strip), subgroup 2 (Sof-Lex discs), subgroup 3 (SuperSnap discs), subgroup 4 (Opti1Step polisher), and subgroup 5 (OneGloss polisher). The specimens were polished in accordance with the manufacturers’ guidelines. The tested resin composite materials were subjected to measurements of surface roughness utilizing a profilometer device. Results: We found statistically significant differences regarding the type of finishing and polishing systems and the type of composite (P < 0.001). All pairwise post hoc analyses showed statistically significant differences (P < 0.05). Conclusions: The type of finishing and polishing systems and the type of composite significantly affect surface roughness. The Mylar strip system showed the lowest surface roughness.